Mabit Sebagai Wahana Pembentukan Identitas Islami Siswa Menuju Usia Pra Remaja SDIT Raudhah Lubuk Basung - Ikhwan Al Hafiz; Martin Kustati; Bashori (PT. Nawa Edukasi Nusantara, 2025)
This study aims to examine how the Mabit program can shape Islamic identity among students at SDIT Raudhah who are in the pre-adolescent age group. The research method used is qualitative. The results indicate that the Mabit program implemented at SDIT Raudhah has a positive impact on forming students’ Islamic identity, such as enhancing spiritual, moral, social awareness, and responsibility. Students at SDIT Raudhah who participated in the Mabit program showed positive behavioral changes and a better understanding of Islamic values. This study also provides recommendations to improve the quality of the Mabit program at SDIT Raudhah and other educational institutions.